2010
DOI: 10.3748/wjg.v16.i33.4176
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent eradication ofHelicobacter pyloriin Japanese patients

Abstract: H. pylori-positive elderly patients should undergo eradication therapy. In addition, it is necessary to improve H. pylori eradication therapy in younger patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 0 publications
2
21
0
Order By: Relevance
“…Some previous studies provide evidence for this result [25,26]. However, the evidence is still debated because of conflicting results [27,28]. A higher likelihood of antibiotics exposure, lower compliance, or additional underlying chronic diseases including diabetes [29] in elderly patients may also explain the result.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Some previous studies provide evidence for this result [25,26]. However, the evidence is still debated because of conflicting results [27,28]. A higher likelihood of antibiotics exposure, lower compliance, or additional underlying chronic diseases including diabetes [29] in elderly patients may also explain the result.…”
Section: Discussionmentioning
confidence: 98%
“…ithromycin for H. pylori was significantly higher than the first-line resistance [14,23]. However, the evidence is still debated because of conflicting results [27,28]. In summation, as antibiotic use is generally accepted as the main factor determining antibiotics resistance, macrolide-resistant H. pylori following previous macrolide exposure might be the main cause of the low eradication rate in Jeju province, although there is still no data on the resistance rate of clarithromycin prepared by the agar dilution method in Jeju province.…”
Section: Discussionmentioning
confidence: 99%
“…Elderly patients generally have many medications prescribed, often suffer from cognitive decline, and frequently have physical limitations, which would affect their medication compliance and possibly result in unsuccessful outcome of therapies . Nevertheless, Mamori et al previously investigated the general risk factors that affected outcome of eradication therapy in Japanese patients, and found that the success rate in patients aged >70 years were over 90%, which was higher than those in younger‐aged groups. This report was contrary to our findings.…”
Section: Discussionmentioning
confidence: 99%
“…16 Infection by this bacterium could potentially result in various gastroduodenal diseases such as peptic ulcer, functional dyspepsia, MALT lymphoma, and [23][24][25] compare the accuracy of the UBT to several other invasive diagnostic tests such as gastric biopsies performed during endoscopy (rapid urease test, histology, culture) and a large number of papers [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] have focused on the efficacy of eradication therapy and the selection of alternate therapies. 16 Infection by this bacterium could potentially result in various gastroduodenal diseases such as peptic ulcer, functional dyspepsia, MALT lymphoma, and [23][24][25] compare the accuracy of the UBT to several other invasive diagnostic tests such as gastric biopsies performed during endoscopy (rapid urease test, histology, culture) and a large number of papers [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]…”
Section: Urea Breath Test (Ubt)mentioning
confidence: 99%